Emergency Medical Equipment On Board German Airliners. Issue 5 (6th June 2014) - Hinkelbein, Jochen; Neuhaus, Christopher; Wetsch, Wolfgang A.; Spelten, Oliver; Picker, Susanne; Böttiger, Bernd W.; Gathof, Birgit S.
<x xml:space="preserve">Abstract</x> Background Medical emergencies often occur on commercial airline flights, but valid data on their causes and consequences are rare. Therefore, it is unclear what emergency medical equipment is necessary. Although a minimum standard for medical equipment is defined in regulations, additional material is not standardized and may vary significantly between different airlines. Methods German airlines operating aircrafts with more than 30 seats were selected and interviewed with a 5‐page written questionnaire between August 2011 and January 2012. Besides pre‐packed and required emergency medical material, drugs, medical devices, and equipment lists were queried. If no reply was received, airlines were contacted another three times by e‐mail and/or phone. Descriptive analysis was used for data presentation and interpretation. Result From a total of 73 German airlines, 58 were excluded from analysis (eg, those not providing passenger transport). Fifteen airlines were contacted and data of 13 airlines were available for analysis (two airlines did not participate). A first aid kit was available on all airlines. Seven airlines reported having a doctor's kit, and another four provided an "emergency medical kit." Four airlines provided an automated external defibrillator (AED)/electrocardiogram (ECG). While six airlines reported providing anesthesia drugs, a laryngoscope, and endotracheal tubes, another four airlines did not provide even a resuscitator bag. One airline did not provide any material for cardiopulmonary resuscitation (CPR). Conclusions Although the minimal material required according to European aviation regulations is provided by all airlines for medical emergencies, there are significant differences in the provision of additional material. The equipment on most airlines is not sufficient for the treatment of specific emergencies according to published medical guidelines (eg, for CPR or acute myocardial infarction).